Magnetism: a very short introduction - Blundell, Stephen (Very short introductions, 2012)
"In this Very Short Introduction, Stephen J. Blundell illuminates the mysterious force of magnetism. For centuries, magnetism has been used for various purposes--through compasses it gave us the ability to navigate, and through motors, generators, and turbines, it has given us power. Blundell explores our understanding of electricity and magnetism, from the work of Galvani, Ampere, Faraday, and Tesla, and describes how Maxwell and Faraday's work led to the unification of electricity and magnetism--one of the most imaginative developments in theoretical physics. Finally, he discusses the relationship between magnetism and relativity, quantum magnetism, and its impact on computers and information storage, showing how magnetism has changed our fundamental understanding of the Universe." -- Publisher's description.